Early detection of neurological disorders using machine learning systems - Paul, Sudip, 1984-; Bhattacharya, Pallab, 1978-; Bit, Arindam, 1985- (Advances in medical technologies and clinical practice book series., 2019)
"This book examines the role of machine learning systems in the detection of neurological disorders such as Alzheimer disease, Parkinson's disease, schizophrenia, and depression"--Provided by publisher.